Preparation method of tin oxide film through staged chemical bath deposition and application of tin oxide film
Through the staged chemical water bath deposition process, the problem that traditional CBD processes are difficult to independently control the performance of tin oxide films is solved, and ultra-thin, dense and conformal growth of tin oxide films is achieved, which significantly improves the photovoltaic performance of perovskite solar cells .
Patent Information
- Application Number
- CN202411422053.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-18
AI Technical Summary
When preparing tin oxide films, traditional chemical water bath deposition (CBD) is difficult to independently control multiple performance indicators, such as thickness, density, morphology and energy band structure, resulting in the performance of the tin oxide layer being limited by reaction time, which makes it difficult to Improve the performance of perovskite solar cells.
Using a staged chemical water bath deposition process (SCBD), the preparation of tin oxide films with ultrathin, dense and conformal growth is achieved by deposition of tin oxide films in stages without destroying the container sealing conditions, skipping the early high oxygen partial pressure stage. .
Through the phased deposition method, the thickness, density, morphology and energy level structure of the tin oxide film can be simultaneously adjusted, which significantly improves the quality of the tin oxide film. It is applied in perovskite solar cells and achieves a photoelectric conversion efficiency of up to 25.46% , the filling factor reaches 0.850, and has excellent photovoltaic performance.
Smart Images

Figure CN119465108A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemistry and photovoltaics, and in particular relates to a preparation method of a tin oxide film deposited by a staged chemical bath and an application thereof. Background Art
[0002] In the past decade, organic-inorganic hybrid perovskite solar cells (PSCs) have achieved rapid development and their photoelectric conversion efficiency (PCE) has been continuously improved. As one of the most promising photovoltaic technologies, perovskite solar cells have unique advantages over other similar products, such as easy manufacturing, low production cost, and compatibility with flexible electronic products, making them still very competitive compared with silicon-based solar cells, which dominate the photovoltaic field. At present, efficient PSCs are mostly made of tin oxide (SnO) prepared by chemical bath deposition (CBD). x ) is used as the formal planar structure of the electron transport layer. The PCE of small-area PSCs prepared based on this process is relatively high, and it has very broad prospects for industrial application.
[0003] Traditional CBD solutions contain hydrochloric acid, urea, thioglycolic acid, stannous chloride dihydrate and water. x The energy band structure of the film is determined by the ion valence state of tin, so the CBD reaction needs to be carried out in a closed container to achieve a low oxygen partial pressure in the container. In order to keep the container airtight, the hydrolysis process needs to be carried out continuously, which makes it difficult to control the reaction process without affecting the reaction progress. For this reason, the specific reaction time in the traditional CBD process has become a key factor in the preparation of SnO with excellent performance. x Tin oxide is the key or even the only parameter of the film, which affects multiple performance indicators such as thickness, morphology, density and band structure. In efficient PSCs, the tin oxide layer needs to have the characteristics of ultra-thinness, conformal growth, high density and band matching. However, the optimal time corresponding to each performance indicator of the tin oxide layer is usually different, which makes it difficult for the performance of the tin oxide layer to break through the constraint of reaction time, which limits the improvement of PSCs performance. The thickness of tin oxide gradually increases with the reaction time. In order to prepare an ultra-thin tin oxide layer, the optimal time associated with the thickness corresponds to the formation of a dense tin oxide layer, but the energy bands of tin oxide often do not match at this time. The oxygen partial pressure gradually decreases with time. In order to meet the low oxygen partial pressure, the reaction time has to be extended, resulting in SnO x The layer is thickened, which in turn hinders the transfer of charges. In addition, the large-sized precipitates produced during hydrolysis in the traditional CBD process will be adsorbed on the substrate surface, making it difficult to prepare a conformal tin oxide layer. The above problems are all due to the difficulty of the existing CBD process to independently control multiple performance indicators, which greatly restricts the performance of tin oxide.
[0004] Therefore, it is urgent to develop a simple method to remove the mutual constraints of performance indicators as a new strategy to analyze and understand the hydrolysis process of tin oxide, so as to further improve the performance of SnO x The quality of the films is particularly important for optimizing the performance of PSCs. Summary of the invention
[0005] The present invention aims to solve one of the technical problems existing in the prior art. To this end, the present invention proposes a preparation method of a tin oxide film deposited by a staged chemical bath and its application, wherein the preparation method can simultaneously control the thickness, density, morphology and energy level structure associated with the time parameter to improve the quality of the tin oxide film. The prepared tin oxide film is applied to the electron transport layer of a perovskite solar cell to prepare a device with excellent photovoltaic performance.
[0006] The inventive concept of the present invention is: by adopting a staged chemical water bath deposition process (SCBD), without destroying the closed condition of the container, the segmented deposition of the material is achieved, so that the deposition process of tin oxide skips the stage of high oxygen partial pressure in the early stage, that is, after the CBD solution is pre-reacted for a period of time, it is brought into contact with the conductive substrate, and then the reaction is continued for a period of time, and an ultra-thin, dense and conformal tin oxide film can be prepared. This method avoids the large particles generated in the high oxygen partial pressure stage affecting the conformal growth and abnormal increase of the thickness of tin oxide. At the same time, by controlling the end point of the reaction, the energy level structure is controlled, and then the thickness, density, morphology and energy level structure associated with the time parameter are simultaneously regulated to improve the quality of the tin oxide film. The staged chemical water bath deposition process of the present invention is a new method for analyzing and understanding the hydrolysis process and optimizing and improving the quality of the film. The tin oxide film prepared based on this method is used as an electron transport layer in perovskite solar cells, which can achieve a photoelectric conversion efficiency of up to 25.46%, a fill factor of 0.850, and excellent photovoltaic performance.
[0007] In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing a tin oxide thin film, comprising the following steps:
[0008] (1) placing a conductive substrate with the conductive surface facing downward at the bottom of a first reaction container, and then placing a second reaction container inside the first reaction container, wherein the second reaction container is filled with a tin oxide precursor solution, and sealing the first reaction container;
[0009] (2) heating the sealed first reaction container, and then tilting the first reaction container to allow the tin oxide precursor solution in the second reaction container to flow into the first reaction container until the conductive substrate is immersed, and then keeping the temperature; taking out the conductive substrate, cleaning, drying, and performing annealing treatment to obtain the deposited tin oxide film on the conductive substrate.
[0010] The staged deposition method of the present invention uses the contact of the tin oxide precursor solution with the conductive substrate as the segmented time point, and divides the deposition reaction into two stages, the segmented time point as the starting point of the staged deposition of the tin oxide film. The segmented time point and the reaction termination time point are adjusted at the same time to achieve simultaneous regulation of multiple parameters of the tin oxide film associated with the reaction time (such as morphology, density, thickness and energy level structure).
[0011] Specifically, the morphology of tin oxide is affected by the size of the precipitate in the solution. Before the tin oxide precursor solution contacts the conductive substrate, the second reaction vessel is in a high oxygen partial pressure state. At this time, the solution is turbid and has more large-sized precipitates. When the oxygen partial pressure is consumed to a lower level, the particles settle to the bottom of the second container. At this time, the conductive substrate will not adsorb large-sized precipitates when it contacts the tin oxide precursor solution, so that the morphology of the formed tin oxide film presents good conformal growth characteristics. The density of tin oxide is the coverage of the conductive layer of the conductive substrate by the tin oxide film, and the optimal reaction time corresponding to the density is the time required to achieve complete coverage. The thickness of tin oxide gradually thickens with the extension of the reaction time. An overly thick tin oxide film is not conducive to the conduction of charge. The optimal reaction time corresponding to the thickness is the time when the tin oxide film just completely covers the conductive substrate, and it has the characteristics of high density and ultra-thin at the same time. The energy level structure of tin oxide is affected by the oxygen partial pressure, wherein the oxygen partial pressure gradually decreases with the extension of the reaction time, and it usually takes a relatively long reaction time to achieve a perfect energy level structure.
[0012] Preferably, in step (2), the heating temperature is 80-95°C.
[0013] Preferably, in step (2), the heating time is 1.5-2.5 hours.
[0014] Preferably, in step (2), the insulation time is 1-2 hours.
[0015] Preferably, in step (2), the temperature of the annealing treatment is 150-240°C.
[0016] Preferably, in step (2), the annealing treatment time is 0.5-1.5 hours.
[0017] Preferably, the second reaction vessel is smaller in size than the first reaction vessel.
[0018] Preferably, the second reaction container is fixed to an inner wall of one side of the first reaction container and may be fixed by a buckle.
[0019] Preferably, the preparation steps of the tin oxide precursor solution are:
[0020] Deionized water, hydrochloric acid, stannous chloride dihydrate, urea and thioglycolic acid are mixed, and stirring is continued in an ice water bath during the mixing process; the volume ratio of the deionized water, hydrochloric acid and thioglycolic acid is (300-500):(3-6):(0.07-0.2), the mass ratio of the stannous chloride dihydrate and urea is (1-1.2):(5-6), and the mass volume ratio of the stannous chloride dihydrate to the deionized water is (0.2-0.4) g:100 mL; then the obtained solution is mixed with deionized water in a volume ratio of (0.5-1.2):(1-5) to obtain the tin oxide precursor solution.
[0021] Preferably, in step (1), the conductive substrate is FTO conductive glass treated with ultraviolet ozone (UVO).
[0022] Preferably, the UVO treatment time is 10-25 minutes.
[0023] The second aspect of the present invention provides the application of the above-mentioned method for preparing tin oxide thin film in the preparation of oxide thin film. The staged water bath deposition process of the present invention is universal and can be used to regulate the reaction process and explore the mechanism to simultaneously optimize multiple indicators of the material.
[0024] Preferably, the oxide film includes a titanium dioxide film, a niobium pentoxide film or a zinc oxide film.
[0025] The third aspect of the present invention provides a tin oxide film, which is prepared by the above-mentioned preparation method, and the thickness of the tin oxide film is between 15±1nm. Compared with the traditional one-step method for preparing tin oxide film, the grain size of the tin oxide film prepared by the staged water bath deposition process of the present invention is more uniform and fine, and has the characteristics of ultra-thin, conformal growth and density, which is conducive to improving its photovoltaic performance.
[0026] A fourth aspect of the present invention provides a perovskite solar cell, wherein the perovskite solar cell comprises the above-mentioned tin oxide thin film.
[0027] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0028] (1) The present invention adopts a staged chemical bath deposition method to prepare a tin oxide film. Under the premise of not destroying the airtight condition of the container, the staged deposition of the material is achieved, so that the deposition process of tin oxide skips the stage of high oxygen partial pressure in the early stage, and only deposits in the late reaction stage, so that the surface of the tin oxide film exhibits good conformal growth characteristics. At the same time, the staged chemical bath deposition method can eliminate the mutual influence of multiple time-related indicators, which is convenient for analyzing the performance of tin oxide films deposited in different time periods. Therefore, the growth mechanism of tin oxide films can be intuitively analyzed and understood, and finally a tin oxide film with good conformal growth, ultra-thin, high density, energy level matching and other characteristics is obtained. It is applied to perovskite solar cells and exhibits optimized open circuit voltage and photoelectric conversion efficiency.
[0029] (2) The staged chemical bath deposition method of the present invention is a new method for analyzing and understanding the hydrolysis process and optimizing and improving the quality of the film. The method has good universality and is suitable for preparing other materials that require a closed container for chemical bath reaction, providing a new idea and strategy for the preparation of oxide films. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 A schematic diagram of a reaction vessel and a preparation process for preparing a tin oxide thin film according to the present invention;
[0031] Figure 2 The scanning electron microscope (SEM) cross-sectional images of the tin oxide thin films prepared in Example 1 of the present invention and Comparative Examples 1-2;
[0032] Figure 3 SEM plan views of the tin oxide thin films and conductive substrates prepared in Example 1 of the present invention and Comparative Examples 1-2;
[0033] Figure 4 Cyclic voltammetry curves of the tin oxide thin films and conductive substrates prepared in Example 1 of the present invention and Comparative Examples 1-2;
[0034] Figure 5 It is a reverse scanning current density-voltage (JV) curve of the perovskite solar cell prepared in Example 1 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION
[0035] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0036] Example 1
[0037] A method for preparing a tin oxide thin film comprises the following steps:
[0038] (1) Etching and cleaning of the conductive substrate: Wipe the surface of the FTO conductive glass substrate etched by the femtosecond laser with a dust-free cloth dipped in detergent to remove surface stains until the substrate surface can be wetted by water, then place the substrate in a container containing detergent, deionized water and ethanol and ultrasonicate for 30 minutes each to ensure that the surface of the glass substrate is clean and free of stains. Subsequently, blow dry the glass surface with an air gun, wrap it with a dust-free cloth for standby use, and place it in a UVO cleaning machine for 15 minutes before use to obtain UVO-treated FTO conductive glass;
[0039] (2) Preparation of SnO2 electron transport layer, the reaction container and the schematic diagram of the preparation process are shown in Figure 1 As shown, the specific steps are:
[0040] To a 500mL Shu Niu bottle, add 400mL of deionized water, 5mL of hydrochloric acid, 1.096g of stannous chloride dihydrate, 5g of urea and 100μL of thioglycolic acid in sequence, keep stirring in an ice water bath during the preparation process, and control the temperature at 0-5°C to obtain a mixed solution; take 40mL of the mixed solution and mix it with 200mL of deionized water to obtain a tin oxide precursor solution;
[0041] like Figure 1 As shown in Figure (a), the FTO conductive glass 4 treated in step (1) is placed in the first reaction container 1 with the conductive surface facing downward; the tin oxide precursor solution 5 is added to the second reaction container 2, and then the second reaction container 2 is placed inside the first reaction container 1, and the second reaction container 2 is fixed to the inner wall of the first reaction container 1 with a buckle 3 to seal the container; finally, it is placed in an oven at 90°C and heated for 2 hours.
[0042] like Figure 1 As shown in FIG. 2 (b), the first reaction container 1 is tilted, and the tin oxide precursor solution 5 in the second reaction container 2 flows into the first reaction container 1, so that the tin oxide precursor solution immerses the FTO conductive glass 4.
[0043] like Figure 1 As shown in Figure (c), the first reaction container 1 is laid flat, and the temperature is kept for 1 hour. The FTO conductive glass 4 is taken out, and it is washed with deionized water for 2 minutes, and then ultrasonicated for 60 seconds. The washed FTO conductive glass is blown dry with an air gun; then annealed at 170°C for 1 hour to obtain the FTO conductive glass with a tin oxide film, which is marked as S3 substrate.
[0044] A method for preparing a perovskite solar cell comprises the following steps:
[0045] 1) Preparation of perovskite light-absorbing layer: The perovskite active layer is prepared by the anti-solvent method, and the present invention adopts the FAPbI3 system. The specific formula is: 0.5 mol / L of methylamine hydrochloride, 1.4 mol / L of formamidine hydroiodide and 1.53 mol / L of lead iodide are dissolved in a mixed solvent of N, N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) with a volume ratio of 8:1, and fully oscillated. The S3 substrate is treated with UVO for 15 minutes. Take 35 μL of perovskite precursor droplets on the S3 substrate and use a pipette tip to make it evenly spread, but it cannot touch the FTO conductive glass substrate. The perovskite film of the present invention is prepared by an anti-solvent spin coating method, and the spin coating step is divided into two steps, the first step has a rotation speed of 1000 rpm and a time of 10 seconds; the second step has a rotation speed of 5000 rpm and a time of 30 seconds (both accelerations are 2000 rpm / s), and 120 μL of ethyl acetate solution is added dropwise as an anti-solvent at the tenth second of the second step to obtain a transparent bright orange liquid film. Subsequently, the substrate is placed on a 100° C. hot stage for annealing for 1 hour to obtain a perovskite layer film.
[0046] 2) Preparation of the upper interface layer: 2 mg of i-butylammonium iodide (iBAI) and 2.8 mg of potassium bis(fluorosulfonyl)imide (KFSI) were dissolved in 1 mL of isopropanol / tetrahydrofuran (IPA / THF) mixed solvent (volume ratio 95:5). After the substrate was cooled, 30 μL of iBAI / K-FSI solution was dynamically spin-coated on the FAPbI3 perovskite layer at 5000 rpm, and then annealed at 100 ° C for 10 min to obtain the iBAI / K-FSI upper interface layer.
[0047] 3) Preparation of hole transport layer: Weigh 91.4 mg of Spiro-OMeTAD, dissolve it in 1 mL of chlorobenzene (CB), add 35.6 μL of 4-tert-butylpyridine, 11.4 μL of Co-TFSI solution (300 mg of Co-TFSI dissolved in 1 mL of acetonitrile), 21 μL of Li-TFSI solution (520 mg of Li-TFSI dissolved in 1 mL of acetonitrile), and shake well. After the substrate is cooled to room temperature, 35 μL of the solution is evenly coated on the surface of the perovskite layer at a speed of 4000 rpm, an acceleration of 2000 rpm / s, and a time of 20 seconds to obtain a Spiro-OMeTAD hole transport layer film.
[0048] 4) Preparation of metal back electrode: A layer of 80nm gold (Au) electrode is evaporated on the surface by vacuum evaporation apparatus to obtain a complete device, namely a perovskite solar cell.
[0049] Comparative Example 1
[0050] Referring to the method for preparing the tin oxide thin film of Example 1, only step (2) is changed. The specific steps are as follows:
[0051] Add 400mL of deionized water, 5mL of hydrochloric acid, 1.096g of stannous chloride dihydrate, 5g of urea and 100μL of thioglycolic acid to a 500mL Shu Niu bottle in sequence. Keep stirring in an ice-water bath during the preparation process and control the temperature at 0-5°C to obtain a tin oxide precursor solution. Take 40mL of the solution and mix it with 200mL of deionized water and add it to the reaction container. At the same time, put in the UVO-treated FTO conductive glass, seal the container, and heat it in an oven at 80°C for 1 hour. After the reaction is completed, use deionized water to wash the FTO conductive glass for 2min, followed by ultrasonic treatment for 60 seconds. The cleaned substrate is blown dry with an air gun and annealed at 170°C for 1 hour to obtain an FTO conductive glass with a tin oxide film, marked as C1 substrate.
[0052] The preparation method of the perovskite solar cell of Comparative Example 1 is the same as that of Example 1.
[0053] Comparative Example 2
[0054] Referring to the method for preparing the tin oxide thin film of Example 1, only step (2) is changed. The specific steps are as follows:
[0055] Add 400mL of deionized water, 5mL of hydrochloric acid, 1.096g of stannous chloride dihydrate, 5g of urea and 100μL of thioglycolic acid to a 500mL Shu Niu bottle in sequence, keep stirring in an ice-water bath during the preparation process, and control the temperature at 0-5°C to obtain a tin oxide precursor solution; take 40mL of the solution and mix it with 200mL of deionized water and add it to the reaction container, and put the UVO-treated FTO conductive glass at the same time, seal the container, and heat it in an oven at 90°C for 3 hours. After the reaction is completed, use deionized water to wash the FTO conductive glass for 2min, followed by ultrasonic treatment for 60 seconds. The cleaned substrate is blown dry with an air gun and annealed at 170°C for 1 hour to obtain an FTO conductive glass with a tin oxide film, which is marked as a C3 substrate.
[0056] The preparation method of the perovskite solar cell of Comparative Example 2 is the same as that of Example 1.
[0057] Performance Testing
[0058] 1. Microstructure of tin oxide film
[0059] Figure 2 The SEM cross-sectional images of the tin oxide films prepared in Example 1 and Comparative Examples 1-2 (the scales in each figure are the same), from Figure 2 It can be seen that the tin oxide film (such as Figure 2 -S3) is significantly thinner than the tin oxide film prepared by the one-step deposition method (such as Figure 2 -C1 and Figure 2 -C3). Moreover, the thickness of the tin oxide layer of C3 fluctuates greatly, and the uniformity is poor. The thickness is about 40-70nm and there are many protrusions in the tin oxide layer, indicating that the deposition process lasting 3 hours is not conducive to the control of morphology and thickness. The tin oxide film of the S3 substrate, which only undergoes the deposition process for 1 hour before the end of the entire reaction, shows the characteristics of good conformal growth, and its thickness is uniform, which is 15±1nm, indicating that the morphology and thickness can be controlled by shortening the deposition time to 1 hour. However, according to the traditional one-step deposition method, the tin oxide film of the C1 substrate obtained by the same deposition time of 1 hour is too thin to measure its thickness, indicating that the thickness growth is concentrated between 1 hour and 3 hours.
[0060] Figure 3 The SEM plan views of the tin oxide thin films and conductive substrates prepared in Example 1 of the present invention and Comparative Examples 1-2 (the scales in each figure are the same), from Figure 3 It can be seen that the surface morphology of the tin oxide film prepared by the staged deposition method in Example 1 (such as Figure 3 -S3) compared with the surface morphology of tin oxide films prepared by one-step deposition method (such as Figure 3 -C1 and Figure 3-C3) has been effectively improved. And from the tin oxide morphology of C1, it can be seen that only a small amount of particles are attached to the substrate surface, which indicates that the coverage of tin oxide is not dense enough. There are obvious particle protrusions in the tin oxide morphology of C3, and more large-sized particles are adsorbed on the surface, which is consistent with Figure 2 The cross-sectional morphology of the C3 substrate is relatively undulating, while the tin oxide morphology of S3 is uniformly distributed on the FTO surface in the form of fine granular deposits, which has the characteristics of conformal growth.
[0061] 2. Photovoltaic performance of perovskite solar cells
[0062] The perovskite solar cells prepared in Example 1 and Comparative Examples 1-2 were tested under the conditions of one sun (AM1.5G, 100 mW / cm 2 ), calibrated with standard silicon cells, with a test area of 0.1486cm 2 ,The results of reverse scanning are shown in Table 1.
[0063] Table 1:
[0064] Photovoltaic performance Open circuit voltage(mV) <![CDATA[Short-circuit current density (mA / cm 2 )]]> Fill Factor Photoelectric conversion rate (%) Example 1 1.146 26.12 0.850 25.46 Comparative Example 1 1.001 26.18 0.803 21.04 Comparative Example 2 1.124 25.87 0.817 23.76
[0065] Figure 4 The cyclic voltammetry (CV) curves of the tin oxide thin films and conductive substrates prepared in Example 1 and Comparative Examples 1-2 are shown in FIG. 1 , wherein the horizontal and vertical scales Potential represent voltage. Figure 4 It can be seen that the CV curves of C1 and FTO are both duckbill-shaped characteristic curves, which is due to the redox reaction between the electrolyte and FTO, indicating that the tin oxide film of C1 is not dense enough. The CV curves of C3 and S3 do not show the redox peak of FTO, indicating that the SnO2 films of C3 and S3 are dense and non-porous.
[0066] Figure 5 The reverse scan JV curves of the perovskite solar cells prepared in Example 1 and Comparative Examples 1-2 are shown in Figure 1, wherein the horizontal axis Voltage represents the voltage and the vertical axis Current Density represents the current density. Figure 5 As can be seen from Table 1, the reverse scanning photoelectric conversion efficiency of the battery based on the C1 substrate is 21.04%, with an open circuit voltage of 1.001 V and a short circuit current of 26.18 mA / cm 2 , the fill factor is 0.803. The reverse scanning photoelectric conversion efficiency of the battery based on the C3 substrate is 23.76%, with an open circuit voltage of 1.124V and a short circuit current of 25.87mA / cm 2 , the fill factor is 0.817. The reverse scanning photoelectric conversion efficiency of the battery based on the S3 substrate is 25.46%, with an open circuit voltage of 1.146V and a short circuit current of 26.12mA / cm2 , the filling factor is 0.850.
[0067] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A method for preparing a tin oxide thin film, characterized in that: The following steps are involved: (1) placing a conductive substrate with the conductive surface facing downward at the bottom of a first reaction container, and then placing a second reaction container inside the first reaction container, wherein the second reaction container is filled with a tin oxide precursor solution, and sealing the first reaction container; (2) heating the sealed first reaction container, and then tilting the first reaction container to allow the tin oxide precursor solution in the second reaction container to flow into the first reaction container until the conductive substrate is immersed, and then keeping the temperature; taking out the conductive substrate, cleaning, drying, and performing annealing treatment to obtain the deposited tin oxide film on the conductive substrate.
2. The method for preparing a tin oxide thin film according to claim 1, characterized in that: In step (2), the heating temperature is 80-95° C.; and / or the heating time is 1.5-2.5 hours.
3. The method for preparing a tin oxide thin film according to claim 1, characterized in that: In step (2), the insulation time is 1-2 hours.
4. The method for preparing a tin oxide thin film according to claim 1, characterized in that: In step (2), the annealing treatment temperature is 150-240° C.; and / or the annealing treatment time is 0.5-1.5 hours.
5. The method for preparing a tin oxide thin film according to claim 1, characterized in that: The size of the second reaction container is smaller than that of the first reaction container; and / or the second reaction container is fixed to an inner wall of one side of the first reaction container.
6. The method for preparing a tin oxide thin film according to claim 1, characterized in that: The preparation steps of the tin oxide precursor solution are: Deionized water, hydrochloric acid, stannous chloride dihydrate, urea and thioglycolic acid are mixed, and stirring is continued in an ice water bath during the mixing process; the volume ratio of the deionized water, hydrochloric acid and thioglycolic acid is (300-500):(3-6):(0.07-0.2), the mass ratio of the stannous chloride dihydrate and urea is (1-1.2):(5-6), and the mass volume ratio of the stannous chloride dihydrate to the deionized water is (0.2-0.4) g:100 mL; then the obtained solution is mixed with deionized water in a volume ratio of (0.5-1.2):(1-5) to obtain the tin oxide precursor solution.
7. The method for preparing a tin oxide thin film according to claim 1, characterized in that: In step (1), the conductive substrate is FTO conductive glass treated with ultraviolet ozone.
8. Use of the method for preparing a tin oxide thin film according to any one of claims 1 to 7 in preparing an oxide thin film.
9. A tin oxide thin film, characterized in that: The tin oxide film is prepared by the preparation method according to any one of claims 1 to 7, and the thickness of the tin oxide film is between 15±1 nm.
10. A perovskite solar cell, characterized in that: The perovskite solar cell comprises the tin oxide thin film according to claim 9.